2008
DOI: 10.1111/j.1600-0463.2008.00995.x
|View full text |Cite
|
Sign up to set email alerts
|

Achromobacter xylosoxidans respiratory tract infections in cystic fibrosis patients

Abstract: Achromobacter xylosoxidans is a ubiquitous Gram‐negative non‐fermenting rod, recently characterized as an emerging pathogen in cystic fibrosis (CF) patients. Its pathogenic potential and prevalent transmission routes are still unclear. This study investigated the PFGE genetic pattern and antimicrobial resistance profile of 42 A. xylosoxidans isolates obtained over 4 years from the respiratory tract of 22 CF patients. By genotypic analysis, 31 isolates were attributed to 8 distinct PFGE patterns (A–H), whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 20 publications
6
55
1
Order By: Relevance
“…An increased need for antimicrobials (11) and hospitalization (26) have also been reported. We found no evidence of clinical decline (lung function loss or risk of PEx) following infection, nor was there a significant change in nutritional status (BMI) over the course of follow-up, similar to the results of a previous study (12). It may be valuable to follow-up with patients for a longer duration to see if such correlations become evident.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…An increased need for antimicrobials (11) and hospitalization (26) have also been reported. We found no evidence of clinical decline (lung function loss or risk of PEx) following infection, nor was there a significant change in nutritional status (BMI) over the course of follow-up, similar to the results of a previous study (12). It may be valuable to follow-up with patients for a longer duration to see if such correlations become evident.…”
Section: Discussionsupporting
confidence: 70%
“…The cumulative prevalence of Achromobacter isolation of 11% in our center is comparable to those previously reported for small centers, which ranged from 5 to 29% (11,12), although this spans 3 decades, making the incidence of infection very low. While others have reported that older patients and patients with greater lung disease burden appear to be predisposed to infection with Achromobacter species (11, 18), we did not observe any correlation between age, nutritional status, CF comorbidities, baseline lung status, or home oxygen use and incident infection.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…It is well known that A. xylosoxidans can cross-infect patients (15,19,21,22,25,27,36). In several cases we found strains of Achromobacter with identical sequences at all five MLSA loci.…”
Section: Mlsamentioning
confidence: 73%